Pertumbuhan Ekonomi Dan Inflasi Di Indonesia Pada Masa Pandemi - Purnama Sari, Eka; Salsabila Rahmawan, Fadia; Jannah , Nurul (Rifa'Institute, 2021)
The Covid-19 pandemic has caused recessions in many countries around the world. This happened after economic growth in the first and second quarters of 2020. Some of the countries experiencing recession are Singapore, South Korea, Germany, Japan, France, Hong Kong, and the United States. If the economic growth in each quarter is also negative, Indonesia will experience a recession. The Central Statistics Agency (BPS) noted that Indonesia's economic growth rate fell to minus (5.32%) in the second quarter of 2020. Previously, Indonesia's economic growth in the first quarter of 2020 was 2.97% or started to slow down. Inflation is a tendency to increase the prices of goods and services in general, which continues continuously, which will reduce the purchasing power of the public, especially for low-income groups. Therefore, it is hoped that there will be a control over the rate of inflation, especially during the Covid 19 Pandemic which had an impact on Indonesia's macro conditions. This observation discusses